Pembaharuan Prosedur Departemen Produksi dan Departemen QSHE di PT Charoen Pokphand Indonesia Balaraja - Chandra, Genesius; Halim, Siana (Jurnal Titra, 2013)
PT Charoen Pokphand Indonesia Balaraja is a company in feed production. One of the ways for PT Charoen Pokphand Indonesia maintaining their feed quality is through documentation of all activity that related with production in procedure. The last update of procedures was in 2008, so some procedures are no longer applicable in companyâs current condition. So that, the procedures must be updated and those procedures can be used as work guidance and work standard. Total of 8 procedures, 34 work instructions, 14 forms, 10 appendixes in Production Department and 13 procedures, 109 work instructions, 31 forms, 7 appendixes in QSHE Department, which had been revised.